Masalah Regulasi dan Pengawasan dalam Praktik Korupsi Haji Tahun 2010-2013 - Firdaus, Bayu (Jurnal Politik, 2017)
The problem of corruption has occurred in many government institutions. Corruption is not only occurred in legislative institutions such as DPR, DPD, or DPRD, but also in executive institutions, such as ministries. Corruption in the Ministry of Religious Affairs is chosen to be explored in this paper because of its supposedly commitment and tightly intricate with moral and religious values to oppose any practices of corruption. This paper argues that the practice of corruption in pilgrim seasons of 2010-2013 occurred due to opportunity made available by problematic regulation and abused of supervision by members of DPR. Previous research found that corruption in Indonesia can be divided into three different causes, which are problems of system or regulation, mental, and both of them. This article looks deeply into the factor of system further and offers two important aspects related to this, which are problematic regulation and abuse of legislative supervision. Both have provided opportunities to the practice of corruption in the ministry. This paper also reviews opportunity factor in GONE theory by Bologna.